Factors Affecting Reading Narrative Ability in SMPN 7 Medan - Sarah Ebrina Br Mataniari; Brigita Br Manurung; Kristin Pasaribu; Putri Palentin Tambunan; Ira Maria Fran Lumbanbatu; Yenita Br Sembiring (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
Reading narrative texts is a vital component of English learning at the junior high school level, as it helps students understand story structures, characters, and moral lessons. However, many students still face difficulties in comprehending these texts effectively. This study aims to identify and analyze the internal and external factors that influence the narrative reading abilities of eighth-grade students at SMP Negeri 7 Medan. Using a descriptive qualitative approach, the research involved 24 students selected through purposive sampling. Data were collected through questionnaires and interviews focused on students’ reading motivation, interest, vocabulary mastery, teaching strategies, parental support, and the classroom environment. The findings indicate that internal factors, particularly motivation to read and the use of effective learning strategies, significantly influence reading performance. Approximately 70% of students with high reading motivation and strategic reading habits showed better comprehension of narrative elements. External factors such as parental support and a supportive learning environment also played a key role, benefiting around 60% of the participants. Students with access to reading materials at home and school, along with encouragement from parents and teachers, demonstrated stronger reading abilities. These results suggest that improving narrative reading skills requires a combined focus on nurturing students’ internal motivation and strengthening external support systems. The implication of this study is that educators should integrate motivational reading strategies and create literacy-rich environments, while parents are encouraged to actively support reading habits at home to enhance students' overall literacy development.